CARBON DIOXIDE EMISSION AMOUNT ESTIMATION SYSTEM AND CARBON DIOXIDE EMISSION AMOUNT ESTIMATION METHOD - MOCHINO Eiko; MATSUMOTO Kentaro (2024)
A carbon dioxide emission amount estimation system (1) comprises: an arithmetic unit (81) that estimates the amount of carbon dioxide emitted from an estimation-subject machine (3) when the estimation-subject machine carries out machining according to a machining program used by an actual processing machine (2); a machining program database (4); an actual processing machine machining condition database (5); and an estimation-subject machine database (6). The arithmetic unit (81): searches the estimation-subject machine database (6); extracts a machining condition for the estimation-subject machine (3), such condition being in common with the machining conditions of the actual processing machine (2) used when the actual processing machine (2) carried out machining according to a machining program; analyzes the machining program used by the actual processing machine (2); predicts, on the assumption that the machining program is executed with the extracted machining condition of the estimation-subject machine (3), the machining time which is the time required for machining by the estimation-subject machine (3); and estimates the carbon dioxide emission amount of the estimation-subjectn machine (3) on the basis of the predicted machining time. Un système d'estimation de quantité d'émission de dioxyde de carbone (1) comprend : une unité arithmétique (81) qui estime la quantité de dioxyde de carbone émise par une machine d'estimation sujet (3) lorsque la machine d'estimation sujet effectue un usinage selon un programme d'usinage utilisé par une machine de traitement réelle (2) ; une base de données de programme d'usinage (4) ; une base de données de conditions d'usinage de machine de traitement réelle (5) ; et une base de données de machine d'estimation sujet (6). L'unité arithmétique (81) : recherche la base de données de machine d'estimation sujet (6) ; extrait une condition d'usinage pour la machine d'estimation sujet (3), une telle condition étant en commun avec les conditions d'usinage de la machine de traitement réelle (2) utilisée lorsque la machine de traitement réelle (2) a effectué un usinage selon un programme d'usinage ; analyse le programme d'usinage utilisé par la machine de traitement réelle (2) ; prédit, en supposant que le programme d'usinage est exécuté avec l'état d'usinage extrait de la machine d'estimation sujet (3), le temps d'usinage qui est le temps requis pour l'usinage par la machine d'estimation sujet (3) ; et estime la quantité d'émission de dioxyde de carbone de la machine d'estimation sujet (3) sur la base du temps d'usinage prédit. 二酸化炭素排出量試算システム（１）は、実加工機（２）が利用した加工プログラムに従って、対象機（３）が加工を行うときの二酸化炭素排出量を試算する演算部（８１）と、加工プログラムＤＢ（４）と、実加工機加工条件ＤＢ（５）と、対象機ＤＢ（６）と、を備える。演算部（８１）は、対象機ＤＢ（６）を検索し、実加工機（２）が加工プログラムに従って加工を行ったときの実加工機（２）の加工条件と共通する、対象機（３）の加工条件を抽出し、実加工機（２）が利用した加工プログラムを解析し、抽出された対象機（３）の加工条件を用いて加工プログラムを実行したものと仮定して、対象機（３）が加工に要する加工時間を予測し、予測された加工時間に基づいて、対象機（３）の二酸化炭素排出量を試算する。